The relationship between insider trading and volume-induced return autocorrelation - Aaron Gilbert; Alireza Tourani Rad; Tomasz Piotr Wisniewski (European University Viadrina, The Postgraduate Research Programme: Capital Markets and Finance in the Enlarged Europe, 2005)
As was establihed in Llorenteetal (2001) the dynamic relationship between return and volume is a function of information asymmetry. This study extends their analysis by linking the volume induced return auto correlarion coefficients with the level of disclosed insider trading. Using New Zealand data, we document a strong link between the sustainability of tradegenerated price changes and the extent of insidertrading. This relationship is robust to alternative econometric specifications and remains significant even after controlling for conventional measure of information asymmetry such as bid-ask spreads size ananalyst following. This suggests that volume induced autocorrelation may be a suitable criterion on which to rank firms on the level of private information trading.
Keywords: G14; C22; 330; Insidertrading; return autocorrelation